(untitled) (OverHolland, 2018)
Ezio Bonfanti’s essay Elementi e costruzione: note sull’architettura di Aldo Rossi (1970) can be regarded as one of the most advanced critiques of Rossi’s work. He examines Rossi’s projects, their inherent analytical characteristics, the relationship with a theory based on the possibilities for describing a project and (more specifically) describing it through an analysis that has to be conducted at the level of the composition. Bonfanti’s contribution can equally be regarded as a broader reflection on fundamental aspects of the discipline, for which he believes Rossi’s work is particularly suited. The two paths thus defined – one studying Rossi’s architecture and the other proposing a scheme for an analytical approach to architecture – therefore mean that the purpose and the subject of the investigation nearly overlap, albeit not to the point of a mise en abyme.